2009
DOI: 10.2337/dc08-1908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structured Versus Usual Care on Renal Endpoint in Type 2 Diabetes: The SURE Study

Abstract: OBJECTIVEMultifaceted care has been shown to reduce mortality and complications in type 2 diabetes. We hypothesized that structured care would reduce renal complications in type 2 diabetes.RESEARCH DESIGN AND METHODSA total of 205 Chinese type 2 diabetic patients from nine public hospitals who had plasma creatinine levels of 150–350 μmol/l were randomly assigned to receive structured care (n = 104) or usual care (n = 101) for 2 years. The structured care group was managed according to a prespecified protocol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
127
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 23 publications
3
127
0
7
Order By: Relevance
“…Moreover, similar cut points have been used in previous studies of multifactorial risk factor management programs. 8 The data presented represent a post hoc exploratory analysis, and no a priori power calculation had been performed. The 3 groups were compared using χ 2 tests, Wilcoxon signed-rank test, or analysis of variance as appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, similar cut points have been used in previous studies of multifactorial risk factor management programs. 8 The data presented represent a post hoc exploratory analysis, and no a priori power calculation had been performed. The 3 groups were compared using χ 2 tests, Wilcoxon signed-rank test, or analysis of variance as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…5 Intensified, multifactorial interventions using behavioral and pharmacological therapy targeting modifiable risk factors such as hypertension, dyslipidemia, and hyperglycemia may reduce both microvascular and macrovascular complications by up to 50%. [6][7][8] Previously, we have demonstrated that a similar intervention promoting healthy behaviors and applying pharmacological algorithms can be delivered by local multidisciplinary teams in a community setting to improve blood pressure, glycemic control, and dyslipidemia, utilizing nonphysician staff to maintain regular follow-ups and ensure adherence with pharmacotherapy and lifestyle changes. 9 In general, such interventions are evaluated by examining whether targets are achieved for individual outcomes for the study population as a whole.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier stages of CKD, weight loss is associated with reduced albuminuria and a slowing decline in kidney function (172). While addressing single risk factors or even a few together may be effective, targeting multiple risk factors concomitantly can result in dramatic reductions in microvascular and macrovascular complications (165,166,(173)(174)(175). Although new therapies hold promise for improving outcomes among patients with DKD, simultaneous control of multiple conventional risk factors effectively reduces the high risks of ESRD, CVD events, and death (4,20).…”
Section: Treatment Of Hypertension and Dkdmentioning
confidence: 99%
“…Possibly, even older drugs such as allopurinol may be shown to play an important role in ameliorating the progression of diabetic CKD in future years. However, it should be remembered that in patients at high risk for the development of progressive diabetic CKD, using existing therapies as part of a targetdriven, intensive, multifactorial intervention results in a reduced risk of CV death and progression to ESRD, as shown in the STENO-2 and other studies [69,70].…”
Section: Discussionmentioning
confidence: 99%